STUDY OF CHEMOPREVENTIVE ROLE OF PADDY HUSK ON CERVICAL ADENOCARCINOMA HUMAN CELL LINE (HELA CELLS) - Shayla Kabir; Jahan, Sarder Mohammad Shahriar; Nowshin, Sazia; Haque, Mohammad Mominul; Islam, Jahidul (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Cervical cancer is the fourth most prevalent cancer type and the fourth primary cause of cancer-related death among women worldwide. The deficiencies of current treatments, including severe side effects and the inability to prevent progression to the metastatic stage, necessitate the investigation of alternative agents. Methods: The chemopreventive approach employing natural products such as Paddy Husk is acquiring considerable traction in the scientific community. This study examined the chemopreventive effects of Paddy Husk on HeLa cervical cancer cells. Using the TBEA method, the IC50 of the husk was determined. To evaluate the antiproliferative activity with prolonged treatment exposure, HeLa cells treated with the IC50 value were incubated for 8 days. Results: The results demonstrated that Paddy Husk extract effectively inhibited the proliferation of HeLa cells throughout the duration of the treatment. Examination under the microscope revealed that Paddy Husk extract induces apoptotic characteristics, including cell contraction, membrane rounding, membrane blebbing, the formation of apoptotic bodies, and vacuolation. A mouse skin fibroblast cell line (L929) was used to assess the in vitro safety of paddy refuse extracts at various concentrations, revealing no toxic effects on normal L929 cells. Conclusion: These findings are essential for advancing our knowledge and recognizing the potential function of Paddy Husk compounds in cervical cancer chemoprevention.